In vitro screening of chrysanthemum (Chrysanthemum morifolium) varieties for salt tolerance - RAI, HENUKA; NAMITA, NAMITA; RAJU, D V S; SINGH, M K; SINGH, KANWAR P; KUMAR, GUNJEET; SINHA, SUBODH KUMAR; S, LEKSHMY; PANDEY, R N; POULOSE, BIBIN (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out to screen six promising varieties of chrysanthemum (Chrysanthemum morifolium Ramat.), viz. Pusa Chitraksha, Lalit, Pusa Aditya, Basanti, Himanshu, and Pusa Sona in MS (Murashige and Skoog) media supplemented with 0, 50, 100 and 150 mM/NaCl. As the concentration of NaCl increased, there was a corresponding decrease in shoot length, fresh weight, number of leaves and rooting percentage. Number of shoots per plant exhibited not much significant difference. Maximum reduction in plant growth was recorded in the variety Pusa Sona (60.60%) while minimum reduction was observed in variety Pusa Aditya (35.60%). The highest fresh weight was recorded in variety Pusa Aditya and lowest in the varieties Himanshu and Pusa Sona, when the medium was supplemented with 150 mM NaCl. Variety Pusa Sona (57.00%) had the maximum reduction in the number of leaves per plant and minimum was found in the variety Lalit (29.10%). Increasing salt stress had an adverse effect on rooting abilities of all the varieties. Under the control with no added NaCl, the rooting percentage was 100% among all the varieties. In medium supplemented with 150 mM/l NaCl, the maximum rooting was recorded in the variety Pusa Aditya (63.80%)) and Basanti (63.80%), whereas least was observed in the varieties Pusa Sona and Himanshu (22.00% and 41.80%, respectively).